Pengaruh Pengungkapan Pertanggungjawaban Sosial Perusahaan (Corporate Social Responsibility Disclosure) Terhadap Earnings Response Coefficient Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010 - Tri Wahyu Karuniawan; Yeterina Widi Nugrahanti (Conference In Business, Accounting, And Management (CBAM), 2012)
The objective of this study is to investigate the effect of Corporate Social Responsibility (CSR) disclosure on Earnings Response Coefficient (ERC). The study hypothesized that there is negative effect of CSR disclosures level on the ERC since the CSR disclosures provide investors more information which is not captured by the accounting earnings. The population in this study is manufacturing companies which is listed on the Indonesia Stock Exchange in 2010. By purposive sampling method, this research obtained 66 companies as the research sample. Dependent variable in this research is the Cummulative Abnormal Return (CAR). Independent variable in this study is interaction between Unexpected Earnings (UE) and CSR diclosures index. Firm size and financial leverage was used as a control variables. For testing the hypothesis, this study using multiple regression analysis. The result found that CSR dislosure have not effect on ERC. While firm size and leverage have positive effect on ERC.Keywords : Â Â Â Corporate Social Responbility (CSR), Earnings Response Coefficient (ERC), Cummulative Abnormal Return (CAR), Unexpected Earnings (UE), Size, Leverage.